ANALISIS KUALITAS JASA PELAYANAN TERHADAP KEPUASAN PASIEN RSU. UNGARAN DI KABUPATEN SEMARANG - Indriyanti, Lies (JURNAL STIE SEMARANG, 2011)
The aims of this research are to know the differences of the service quality in reality and the patients-expected-service quality and to know the influences of service quality (Servqual = Scale multy item by Parasuraman ) dimensions on patients’ satisfactory. Analysis Multiple regresi and hypothesis proofing are done by using difference tesing, T testing, and F testing. Independent Variables  which  are  being  used  are  tangible,  reliability,  responsiveness,  assurances,  and empathy while for  the dependent  variable, we use  patients’  satisfactory.  The  result of this research shows that there is a gap. The gap appears between the patients-expected service qualities and the received service qualities.   This is proved by Paired-Sample T-Test, with significance rate of each variables is 0.05 below the real tariff. The result also shows that the dimensions of service quality influence patients’ satisfactory positively and significantly (Probability score from T Test and F Test are below 0.05). From this research, the researcher hopes that this can be helpful and be an information source for RSU Ungaran so that It will always try to improve its services performance   so it can not only satisfy the patients but also contribute in the region’s incomes.